Phase Evolution and Thermal Stability of Mechanically Alloyed AlCrFeCoNiZn High-Entropy Alloy - Shivam V.; Sanjana V.; Mukhopadhyay N.K. (My University, 2025)
In the present investigation, a newly designed composition of equiatomic AlCrFeCoNiZn high-entropy alloy (HEA) has been synthesized by mechanical alloying. The milled powder after 30 h exhibited the formation of a single solid solution phase of BCC crystal structure with lattice parameter, a = 2.87 ± 0.02 Å. Decomposition of the single-phase BCC structure into the two-phase, tetragonal (Cr–Co)-based σ phase (a = 8.81 Å, c = 4.56 Å)- and L12 (a = 3.59 ± 0.02 Å)-type intermetallics was observed at temperature of ~ 800 °C (1073 K). However, after heat treatment of the 30 h milled powder at the temperatures of 300 °C (573 K) and 600 °C (873 K), similar type of phases was also noticed to coexist along with B2 (a = 2.87 ± 0.03 Å)-type phase. This behaviour of the alloy confirms the diffusive nature of the phase transformation. The consolidated bulk alloy exhibited similar type of phases after sintering at 950 °C (1223 K). © 2020, The Indian Institute of Metals - IIM.